A Cd-MOF as a fluorescent probe for highly selective, sensitive and stable detection of antibiotics in water. Issue 8 (7th March 2019) - Xing, Pengcheng; Wu, Di; Chen, Jingshuai; Song, Jiming; Mao, Changjie; Gao, Yuanhao; Niu, Helin
Abstract : A new MOF as a fluorescent probe for highly selective, sensitive and stable detection of ceftriaxone sodium in water. Abstract : Recently, the pollution and damage caused by antibiotics in water have aroused serious concerns. In this situation, it is extremely important to develop a highly effective approach to detect antibiotics in water. In this contribution, we built a Cd-MOF material with stable fluorescence properties, using bbi = 1, 4-bis(2-methyl-imidazol-1-yl)butane and H2 L = 1, 2-phenylenediacetic acid as organic ligands and Cd(NO3 )2 ·4H2 O as the metal node. The highly selective response of this MOF probe to ceftriaxone sodium (an antibiotic) can reach up to the ppb level in water, along with a fast response time, acid and alkali resistance, and anti-interference ability.